Analisis Kurikulum Pembelajaran di Kuttab Abu Bakar Yayasan Imam Syafi’i Pekan Sabtu Kota Bengkulu - Ridho Sutisyah Putra (UIN Fatmawati Sukarno Bengkulu, 2023)
The purpose of this studi is to find out: first, the design of a learning curriculum at kuttab Abu Bakar Imam Syafi’i Bengkulu? Second, the implementation of the curriculum learning at Kuttab Abu Bakar Imam Syafi’i Bengkulu?. This type of research is descriptive qualitative using a phenomonological approach. The results of this research are: First, the curriculum development model used was The Grass Roots Model (1) The purpose of the curriculum was to create an independent, moral and knowledgeable for Muslim generation. While (2) the contents of the curriculum, namely: memorizing letters, pillars of faith, pillars of Islam, fiqh, adab, morals, recitation and stories of the prophets, (3) learning strategies, is: using methods in the form of lectures, discussions, sirah and talaki. During the learning process, the teacher getting a guide book containing the Islamic learning process. (4) The evaluation of learning at the Kuttab Abu Bakar was carried out twice, namely through a special meet- ing between the teacher and the head of the kuttab, then the second was an evaluation of the students. second, regarding the implementation of the curriculum in kuttab, there are several findings that can be concluded. (1) Learning starts from 07.15 to 13.00 WIB, each class is filled with 24 students, in the implementation of learning using various methods, namely the methods used, can be in the form of lectures, discussions, and talaki, (2) It is known that’s kuttab also teaches general material such as SBK, PJOK, Mathematics etc. (3) There are obstacles in implementing the curriculum for educators, namely, the absence of a library as reading material.